The Effect of Based Services Medication Therapy Management on Treatment Adherence and Quality of Life of Diabetes Mellitus Patients - Rachma Malina; Nanang Munif Yasin; Chairun Wiedyaningsih (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes mellitus is a chronic metabolic disorder that is characterized by hyperglycemia. Diabetes mellitus need appropriate therapeutic management, because it can cause complications. On of the services that can do to improve diabetes control is Medication Therapy Management (MTM). MTM is a new service that will help pharmacist to improve patient adherence and quality of life. This study aims to determine the effect of based services MTM on treatment adherence and quality of life in patients with diabetes mellitus. This study was an experimental study using a quasi-experimental with one group pretest and posttest design which was conducted in Tegalrejo, Jetis and Gedontengen Health Center Yogyakarta City. Variables measured were medication adherence using the Morisky-Green Levine Medication Adherence Scale (MGLS) questionnaire and quality of life using Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ) before and after MTM services. The effect of MTM on medication adherence was analyzed using Wilcoxon test and the effect of MTM on quality of life using Paired T-Test. The patients participate in this study were 20 people, with average score of adherences before application of MTM was 2.20±0.410 to 1.80±0.616 after the application of MTM (P=0.005) and the average of the patient's quality of life was 73.82±7.918, increased to 76.42±5,623 after MTM service (P=0.033). Statistically mean, there is a difference in adherence and quality of life before and after MTM services. Therefore, it can be concluded that MTM-based services performed by pharmacists have a significant effect on improving medication adherence and quality of life for DM patients. Moreover, it can facilitate monitoring patient therapy, and identification of problems related to the treatment.